2014
DOI: 10.1002/2013jf003017
|View full text |Cite
|
Sign up to set email alerts
|

Snow stratigraphic heterogeneity within ground‐based passive microwave radiometer footprints: Implications for emission modeling

Abstract: Two-dimensional measurements of snowpack properties (stratigraphic layering, density, grain size, and temperature) were used as inputs to the multilayer Helsinki University of Technology (HUT) microwave emission model at a centimeter-scale horizontal resolution, across a 4.5 m transect of ground-based passive microwave radiometer footprints near Churchill, Manitoba, Canada. Snowpack stratigraphy was complex (between six and eight layers) with only three layers extending continuously throughout the length of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 63 publications
(126 reference statements)
3
31
0
Order By: Relevance
“…Proksch et al (2015) demonstrated the use of the SMP to reveal spatial density variations in an Antarctic snow profile. Although spatially varying density is a known problem for a broad range of applications (e.g., Rutter et al, 2014), an intercomparison of the ability of different methods to resolve spatial density variations was beyond the scope of the study presented here.…”
Section: Proksch Et Al: Snow Densitymentioning
confidence: 99%
“…Proksch et al (2015) demonstrated the use of the SMP to reveal spatial density variations in an Antarctic snow profile. Although spatially varying density is a known problem for a broad range of applications (e.g., Rutter et al, 2014), an intercomparison of the ability of different methods to resolve spatial density variations was beyond the scope of the study presented here.…”
Section: Proksch Et Al: Snow Densitymentioning
confidence: 99%
“…Therefore, vertical changes of macrostructural parameters, such as temperature and density, are related to the evolution of snow microstructure. However, the structure of snowpack is very complex and spatial variations are large even on a small scale (Rutter et al, 2014;Derksen et al, 2009). Therefore, manual observations of snow macro-and microstructure have an important role in the monitoring of temporal evolution and spatial variations of snowpack.…”
Section: Introductionmentioning
confidence: 99%
“…SNTHERM simulates a grain size that is closer in concept to the visual estimates of grain diameter than the other two models. The large spread when coupling snowpack evolution and microwave models, due to the differences in the modelling of snow microstructure, is consistent with the wide range of studies that have investigated how to link snowpack observations of microstructure to the microstructure parameter required in electromagnetic models (e.g Kendra et al, 1998;Du et al, 2005;Liang et al, 2008;The Cryosphere, 11, 229-246, 2017 www.the-cryosphere.net/11/229/2017/ Durand et al, 2008;Brucker et al, 2011;Xu et al, 2012;Montpetit et al, 2013;Roy et al, 2013;Rutter et al, 2014;Picard et al, 2014). Nevertheless there are differences between microwave emission models for a particular microstructure evolution model and even differences within the same family of emission models.…”
Section: Discussionmentioning
confidence: 53%
“…These fall into different categories, depending on sensor characteristics, the source of the evaluation data (ground-based, airborne, satellite) and presence of ice lenses , the treatment of the snow microstructure (Picard et al, 2014), snow type, observation angle, and the specific electromagnetic model , and the underlying substrate (Lemmetyinen et al, 2009;Derksen et al, 2014). Examples of unscaled field observations of microstructure compared with ground-based observations include the HUT simulations of , who found an RMSE of 10-34 K, and Rutter et al (2014), who found a bias of 34-68 K that was reduced to < 0.6 K upon application of grain scale factors of 2.6-5.3. Scaling, or best-fit, relationships were used by Durand et al (2008) (mean absolute error 3.1 K at V-pol and 9.3 K at H-pol), Montpetit et al (2013) , Brucker et al (2011) (RMSE 1.5 K), Picard et al (2014) (RMSE 1-11 K), and Roy et al (2013) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation